2006
DOI: 10.3727/154427306779435184
|View full text |Cite
|
Sign up to set email alerts
|

Unsustainable Dolphin-watching Tourism in Fiordland, New Zealand

Abstract: Bottlenose dolphins are a key resource of the tourism industry in Fiordland and are used on a daily basis by the tour operators offering cruises on the fiords. Recent studies have shown that the current levels of dolphin–boat interactions in this region cannot be sustained by bottlenose dolphins. Interactions have both short- and long-term effects on both individuals and their populations. Population models indicate that these effects may be affecting the viability of the three bottlenose dolphin populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
89
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(90 citation statements)
references
References 10 publications
1
89
0
Order By: Relevance
“…data) and hence may have joined the population. Current evidence suggests the Dusky Sound population experiences the least human impact of the dolphin populations in Fiordland (Lusseau et al 2006). The lower levels of impact may mean that individuals immigrating to Dusky Sound have a higher chance of survival and successfully joining the new population, compared with those emigrating to join the northern population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…data) and hence may have joined the population. Current evidence suggests the Dusky Sound population experiences the least human impact of the dolphin populations in Fiordland (Lusseau et al 2006). The lower levels of impact may mean that individuals immigrating to Dusky Sound have a higher chance of survival and successfully joining the new population, compared with those emigrating to join the northern population.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary modelling of a long-term data set suaaests that this decline occurred around 2002 Fiordland, New Zealand. and that current levels of calf survival are, to our knowledge, the lowest calf survival rates reported in the literature (Currey et al 2008). The rate of decline in abundance and survival is unsustainable and long-term viability of the population is threatened (Lusseau et al 2006;Currey et al 2007Currey et al , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…But Lusseau's group has also shown that the bottlenose dolphins (Tursiops sp.) in Doubtful Sound, New Zealand, could be driven to extinction in decades 2 . The large number of dolphin-watching trips in the sound is driving the animals away from their preferred areas and forcing them to avoid boats instead of feeding.…”
mentioning
confidence: 99%
“…The potential impact of whale-watching has been studied for more than twenty years (Baker & Herman 1989;Corkeron 2004) and a wide variety of short-term effects have been detected (for example Bejder et al 1999;Au & Green 2000;Nowacek et al 2001;Van Parijs & Corkeron 2001;Williams et al 2002;Hastie et al 2003;Lusseau et al 2006). These include changes in vocalization and respiration patterns, variations in path directedness and other short-term behavioural alterations resulting from apparent horizontal and vertical avoidance tactics (Frid & Dill 2002).…”
Section: Introductionmentioning
confidence: 99%